Durable antibacterial chinlon composite fiber and processing technology thereof

By using silver zeolite antibacterial agents and titanate coupling agents in nylon fibers, the problem of insufficient antibacterial and mechanical properties of traditional nylon fibers is solved, and the long-lasting antibacterial and high mechanical properties of the fibers are achieved, and the processing performance and product added value are improved.

CN119877139AInactive Publication Date: 2025-04-25NANTONG YONGSHENG FIBER NEW MATERIAL
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510377509.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional nylon fibers have shortcomings in antibacterial properties, mechanical properties and processing properties, with poor antibacterial durability, limited improvement in strength and toughness, and it is difficult to accurately control performance indicators in the production process.

Method used

The silver zeolite antibacterial agent is adopted, and the silver ion content is suitable and the gradient is distributed, uniformly dispersed in the nylon matrix material. Combined with titanate coupling agent and polyethylene glycol dispersant, a stable antibacterial agent distribution is formed, which improves the antibacterial uniformity and durability of the fibers, and improves mechanical properties and processing properties by optimizing the cross-sectional shape and surface structure of the fibers.

Benefits of technology

The long-lasting antibacterial properties of the fiber are achieved, and the mechanical properties such as tensile strength and wear resistance are significantly improved, as well as the processing properties of the fiber and product added value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_15
    Figure SMS_15
  • Figure SMS_22
    Figure SMS_22
  • Figure SMS_23
    Figure SMS_23
Patent Text Reader

Abstract

The invention relates to the technical field of fibers, in particular to durable antibacterial polyamide composite fibers and a processing technology thereof.The composite fibers comprise, by weight, 70%-90% of polyamide base materials, 5%-20% of antibacterial agents and 2%-5% of dispersing agents, according to the durable antibacterial polyamide composite fiber, the silver zeolite antibacterial agent is adopted, the content of silver ions is appropriate, the silver ions are distributed in a gradient mode, long-acting antibacterial performance is guaranteed, the silver zeolite antibacterial agent is evenly dispersed in the fiber and regularly arranged in a three-dimensional space, the consistency of different positions is high, bacteria are effectively inhibited, and the durability of the antibacterial polyamide composite fiber is improved. The nylon antibacterial fiber is suitable for antibacterial textiles, antibacterial agent distribution of the fiber is stable, antibacterial uniformity and durability are guaranteed due to the radial and length direction characteristics, meanwhile, the molecular weight and molecular chain structure of the nylon base material provide a good strength and toughness basis for the fiber, the length and distribution of the fiber are reasonable, the shape of the cross section is regular, and stress is uniform when the fiber is stressed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fibers, in particular to a durable antibacterial nylon composite fiber and a processing technology thereof. Background Art

[0002] With the improvement of people's living standards and the emphasis on health, the demand for antibacterial fibers in the textile field is growing. Nylon, as a commonly used fiber material, has good wear resistance, strength and other properties and is widely used in many fields. However, traditional nylon fibers have many shortcomings.

[0003] In terms of antibacterial properties, ordinary nylon fibers lack effective antibacterial functions and are prone to breeding bacteria during use, which not only produces odors but may also pose a threat to human health, such as causing skin allergies and other problems. Although there are some antibacterial fiber products, they have the defect of poor antibacterial durability. Some antibacterial agents have a certain antibacterial effect in the early stage of fiber use, but as time goes by or the number of washings increases, the antibacterial performance decreases rapidly and cannot meet the needs of long-term use.

[0004] From the perspective of physical properties, there are certain limitations in improving the strength and toughness of traditional nylon fibers. Factors such as its molecular structure and molecular weight limit the further development of the fiber in terms of high strength, high wear resistance and other properties. In some application scenarios with high requirements for mechanical properties (such as industrial textiles, high-performance sports equipment, etc.), it cannot fully play its role. At the same time, the cross-sectional shape and dimensional stability of the fiber are not ideal, which leads to problems such as uneven force and deformation during processing and use, affecting product quality and service life.

[0005] In terms of processing performance, it is difficult to accurately control the various performance indicators of nylon fiber in the production process of traditional nylon fiber. The uneven dispersion of additives during the mixing process can easily cause local performance differences; the spinning and post-processing process parameters are difficult to accurately control, resulting in problems such as uneven fiber diameter and rough surface, which reduces the processability of the fiber and the added value of the product.

[0006] In addition, the fiber surface performance needs to be improved. The surface of traditional nylon fibers lacks special functional structures. For example, insufficient surface lubricity leads to limited spinnability and rough feel. It lacks effective antioxidant protection and is easily affected by environmental factors, causing aging and degradation, which shortens the service life of the fiber. The existence of these problems limits the further development of nylon fibers in the field of high-performance and multifunctional textiles. A durable antibacterial nylon composite fiber with better performance and its processing technology are needed to solve the above problems. Summary of the invention

[0007] Technical problem to be solved: In view of the above-mentioned shortcomings of the prior art, the present invention provides a durable antibacterial nylon composite fiber and a processing technology thereof. The durable antibacterial nylon composite fiber of the present invention adopts a silver zeolite antibacterial agent, which has an appropriate silver ion content and is distributed in a gradient manner to ensure long-term antibacterial properties. The silver zeolite antibacterial agent is evenly dispersed in the fiber and regularly arranged in three-dimensional space. The consistency at different positions is strong, which effectively inhibits bacteria and is suitable for antibacterial textiles. The fiber antibacterial agent is stably distributed, and the radial and length direction characteristics ensure the antibacterial uniformity and durability. At the same time, the molecular weight and molecular chain structure of the nylon matrix material provide the fiber with a good strength and toughness foundation. The fiber length and distribution are reasonable, the cross-sectional shape is regular, the stress is uniform when subjected to force, and the mechanical properties such as tensile strength and wear resistance are greatly improved.

[0008] Technical solution: To achieve the above objectives, the present invention is implemented through the following technical solutions: In one aspect, a durable antibacterial nylon composite fiber comprises the following components: Nylon matrix material: accounting for 70-90% of the total weight of the fiber, the nylon matrix material is polyamide 6 or polyamide 66, with a number average molecular weight of 10,000-30,000, a weight average molecular weight of 20,000-50,000, an amide bond content of 90-98% in the molecular chain, and terminal groups including carboxyl and amino groups, with a carboxyl content of 0.1-0.5% and an amino content of 0.05-0.3%; Antimicrobial agent: accounting for 5-20% of the total weight of the fiber, it is an inorganic antimicrobial agent silver zeolite, with an average particle size of 0.5-2μm and a silver ion content of 2-5%. The crystal structure of silver zeolite is cubic, with a lattice constant of 1-2nm. Its surface has a specific microscopic morphology, with a roughness of 0.1-0.3μm, and the distribution of silver ions in the zeolite crystal has a specific gradient, with the concentration of silver ions gradually decreasing from the crystal surface to the interior; Dispersant: accounting for 2-5% of the total weight of the fiber, it is polyethylene glycol, with a molecular weight of 4000-8000, a linear molecular chain, a degree of polymerization of 90-180, and hydroxyl end-capping at both ends. Its dispersion mechanism in the fiber preparation process is based on steric hindrance effect and hydrogen bonding with other components. The mass ratio of dispersant to antibacterial agent is between 1:2-1:5; Coupling agent: accounting for 1-3% of the total weight of the fiber, it is a titanate coupling agent, its molecular structure contains a long-chain alkyl group, the length of the alkyl chain is 8-18 carbon atoms, and it also contains multiple active groups, including carboxyl and phosphate groups, the number of active groups is 2-4, and the molar ratio of the coupling agent to the antibacterial agent is 1:1-1:3; Other additives: accounting for 2-5% of the total weight of the fiber, including antioxidants and lubricants. The antioxidant is a hindered phenol antioxidant, and its chemical structure contains phenolic hydroxyl groups and specific substituents. The substituents include tert-butyl, and the content is 1-3%. The lubricant is calcium stearate, and its particle size is between 1-5μm, and the content is 1-2%.

[0009] Furthermore, the distribution state of the antimicrobial agent is characterized by: In the three-dimensional space of the fiber, the antimicrobial agent exists in the nylon matrix material in the form of discrete particles. The particles are distributed on the cross section of the fiber. A polar coordinate system is established with the center of the circle as the origin. The radial distribution density function of the antimicrobial agent particles is: ,in , , is a constant, is the radius, the angular distribution is uniform, and in the fiber length direction, the distribution of antimicrobial particles conforms to the Poisson distribution, with an average of one particle every 10-20 μm, and a standard deviation of 2-5 μm; From a microscopic perspective, there is an interface layer with a thickness of 0.01-0.05μm between the antimicrobial agent particles and the nylon matrix. This interface layer is formed by the interaction between the coupling agent, the matrix and the antimicrobial agent. The concentration of the coupling agent in the interface layer changes gradually from the surface of the antimicrobial agent to the inside of the matrix, and the gradient change rate is 0.1-0.5mol / cm³・μm. High-resolution transmission electron microscopy observations showed that there was no agglomeration between the antimicrobial particles and the matrix, and sampling at different positions of the fiber showed that the distribution of the antimicrobial particles was highly consistent, with the difference between the sampling positions being less than 5%.

[0010] Furthermore, the cross-sectional shape of the composite fiber has the following characteristics: The cross section is circular or approximately circular, the diameter of the circle is between 10-50 μm, the circularity is between 0.9-1.0, and the circularity calculation formula is: circularity = 4×Π(cross-sectional area) / (circumference²); For circular cross-sections, the fluctuation range of the center position in the axial direction of the fiber is within ±0.5μm, and in the cross-section, the fiber density distribution is centrally symmetrical in the radial direction from the center to the edge, and the density change rate is less than 5% / μm; For the approximately circular cross section, the deviation of its profile from the ideal circle is quantified by the Fourier descriptor. The sum of the absolute values ​​of the first five-order Fourier descriptors is less than 0.1, and the change of this deviation along the fiber length direction is continuous and slow, with a rate of change of less than 0.01 / μm. The boundary of the cross section has specific microscopic geometric characteristics, the average curvature of the boundary is between 0.1-1.0μm-1, and the curvature change at each point on the boundary is continuous, and there is no curvature mutation point.

[0011] Furthermore, the surface structure of the composite fiber has the following characteristics: There is a covering layer with a thickness of 0.1-0.5μm on the fiber surface. This covering layer is composed of multiple components, including some additives that migrate from the inside of the fiber to the surface and substances formed by the interaction with the external environment during processing. The composition ratio of the covering layer changes gradually in the depth direction. The lubricant content in the outer layer close to the fiber surface is higher, accounting for 60-80%, and gradually decreases toward the inner layer, while the antioxidant content is the opposite, decreasing from 80% to 20% from the inside to the outside; The fiber surface covering layer has a nanoscale undulating structure, the height difference of the undulation is between 10-50nm, the wavelength of the undulation is between 50-200nm, and the undulating structure shows a regular pattern under atomic force microscopy. The repeating unit of the pattern is a hexagon or rectangle with a side length between 50-150nm. There are microscopic holes on the surface of the covering layer, the diameter of the holes is between 1-10nm, and the density of the holes is 10 6 -10 8 The holes are evenly distributed on the fiber surface, and the uniformity of the distribution is analyzed by gray-level co-occurrence matrix, with an entropy value between 0.5 and 1.0.

[0012] Furthermore, the length and length distribution of the composite fiber have the following characteristics: The average length of the fiber is between 30 and 100 mm, and its length distribution conforms to the log-normal distribution. The parameters of the log-normal distribution are: the position parameter μ is between 3 and 5, and the scale parameter σ is between 0.5 and 1.0; The fiber length was measured by a laser particle size analyzer with a measurement error within ±2 mm. The fiber sample quantity was greater than 1000 and the skewness of the length distribution was between -0.5 and 0.5, and the kurtosis was between 2 and 4, which ensured the normality of the fiber length distribution. During the fiber production process, the fiber length is controlled by the cutting process. The tool movement accuracy of the cutting equipment is within ±0.1mm, and the tensile or compressive deformation of the fiber during the cutting process is less than 5%.

[0013] On the other hand, a processing technology of a durable antibacterial nylon composite fiber, the specific steps of the processing technology are: S100: a mixing step, in which the antimicrobial agent, dispersant, coupling agent and other additives are mixed in a specific proportion to form a uniform mixed powder; S200: a blending and extruding step, blending and extruding the mixed powder and the nylon matrix material to obtain a melt; S300: Spinning step, allowing the melt to pass through a spinning assembly to form fibers; S400: post-processing step, cooling, oiling, stretching and curling the fiber in sequence, and finally obtaining a durable antibacterial nylon composite fiber.

[0014] Furthermore, step S100 is specifically as follows: S110: Use a specially designed high-speed mixer with a mixing barrel volume of 50-200L. The barrel wall material is stainless steel 304. The inner wall is equipped with a spoiler structure, which consists of a spiral protrusion height of 2-5mm and a groove depth of 1-3mm. The width of the protrusion and groove are both 2-5mm, and the pitch is 10-20mm. S120: Precisely weigh antimicrobial agents, dispersants, coupling agents and other additives within a weighing error of ±0.1%, and then add them to a mixing barrel. The mixing barrel is equipped with a temperature sensor with an accuracy of ±0.5°C, and the temperature in the barrel is maintained at 40-60°C through an external heating jacket; S130: Start the mixer and stir at a speed of 1000-2000 rpm for 10-20 minutes. The stirring paddle is a double-layer three-blade type with a blade inclination angle of 30-60° and a gap of 5-10mm between the blade and the inner wall of the mixing barrel, so that the materials are fully mixed to form a uniform mixed powder.

[0015] Furthermore, step S200 is specifically as follows: S210: Blending and extrusion are carried out in a twin-screw extruder, the screw diameter of the twin-screw extruder is 30-60mm, the screw aspect ratio is 30-40:1, the screw material is high-strength alloy steel, the hardness is HRC50-60, the surface is nitrided, the nitrided layer depth is 0.1-0.3mm, and the surface roughness is 0.05-0.1μm; S220: The screws rotate in the same direction, and the speed can be adjusted within the range of 100-300 rpm, with an adjustment accuracy of ±1 rpm. The screw is divided into a feeding section, a compression section, a melting section and a metering section, and the length ratio of each section is 1:2:3:2. In the feeding section, the pitch is 30-40mm, the screw groove depth is 5-10mm, the temperature is controlled at 200-220℃, and a vacuum feeding system is used. The feeding accuracy is ±0.5%. In the compression section, the pitch is gradually reduced to 20-30mm, and the screw groove depth is correspondingly reduced to 3-6mm. The temperature Increase to 230-250℃, compression ratio is 2-3, in the melting section, the temperature is further increased to 240-260℃, and real-time monitoring is carried out by a temperature sensor with an accuracy of ±0.5℃ and a pressure sensor with a monitoring range of 0-100MPa and an accuracy of ±0.1MPa installed inside the screw. In the metering section, the pitch and screw groove depth remain stable, 20-30mm and 3-6mm respectively, the temperature is 250-270℃, and the material extrusion amount is accurately controlled by adjusting the screw speed and back pressure, and the extrusion amount control accuracy is ±1%; S230: adding the mixed powder obtained in step S100 and the nylon matrix material into the twin-screw extruder through respective feeding ports, and achieving co-extrusion under the shearing, mixing and conveying action of the screw to form a uniform melt.

[0016] Furthermore, step S300 is specifically as follows: S310: melt spinning method is adopted, the temperature of the spinning box is stabilized at 240-270°C by using an electric heating power of 10-30kW and a temperature control accuracy of ±1°C, and the melt obtained in step S200 is delivered to the spinning assembly at a stable flow rate by a metering pump with a flow accuracy of ±0.5% and a displacement of 0.1-10ml / r; S320: The filtering device in the spinning assembly is composed of multiple layers of stainless steel 316L filter screens, with mesh sizes of 200, 400 and 600 from the feed end to the discharge end. The thickness of each layer of filter screen is 0.1-0.3mm, and the spacing between adjacent filter screens is 2-5mm. The filtering efficiency of impurities in the melt is greater than 99%; S330: The melt passes through a distribution plate with a thickness of 5-10 mm. A guide groove is provided on the surface of the distribution plate. The depth of the guide groove increases linearly from 0.5-1 mm at the feed end to 1-2 mm at the discharge end, and the width increases from 2-3 mm at the feed end to 3-5 mm at the discharge end. The total number of guide grooves is 10-30 and is evenly distributed. The spacing between adjacent guide grooves is 5-10 mm. The flow rate of the melt in the guide groove is 0.1-0.5 m / s. S340: The melt finally passes through a spinneret, which has a thickness of 3-6 mm, a spinneret hole diameter of 10-50 μm, 100-1000 spinnerets arranged in a circle, and a center distance of adjacent spinnerets of 0.5-2 mm. The inner wall of the spinneret hole is electrochemically polished, and the surface roughness is less than 0.2 μm. Fibers are formed at a spinning speed of 1000-3000 m / min.

[0017] Furthermore, step S400 is specifically as follows: S410: Cooling. The spun fibers are cooled by cooling air provided by the air treatment system. The air treatment system includes an air filter with a filtration accuracy of 0.1-0.5μm, a heating power of 5-15kW, a temperature adjustment accuracy of ±0.5℃, a heater that can control the temperature at 15-25℃, a humidifier that can control the air humidity at 40-60%, and an air volume of 1000-5000m³ / h. The wind speed can be adjusted within the range of 0.5-1.5m / s, and the adjustment accuracy is ±0.05m / s. The fan allows the fibers to be cooled and shaped in a stable environment; S420: Oiling: the cooled fiber is oiled on an oil roller oiling device with an oil roller diameter of 100-300 mm, a length of 200-500 mm, a surface rubber hardness of Shore A60-80, and a rotation speed of 50-100 rpm. The oiling agent is a mixed oil agent with a mass ratio of 3:1:1 of silicone oil, antistatic agent and bioactive additive, and the oiling rate is 0.5-1.5%. The oiling agent is formed into an oil mist with a particle size of 1-5 μm by an ultrasonic atomization device and uniformly adhered to the fiber surface; S430: Stretching: the oiled fiber is stretched between multiple sets of stretching rollers with a diameter of 50-100 mm, chrome-plated surface, roughness of 0.05-0.1 μm, and a spacing of 100-300 mm between each set of stretching rollers. The stretching multiple is 3-5 times, and the stretching temperature is 70-90°C. The stretching is achieved by precisely controlling the roller speed and tension, where the speed accuracy is ±0.5 rpm and the tension accuracy is ±0.1N. S440: Curling: The stretched fiber is curled in a crimping machine with a crimping wheel diameter of 200-500mm, a special texture on the surface, a texture depth of 0.1-0.3mm, and a texture spacing of 1-3mm. The crimping temperature is 80-100℃, and the crimping degree is 10-20 / 25mm. The crimping is achieved by precisely controlling the crimping wheel speed and pressure, with a speed accuracy of ±1 rpm and a pressure accuracy of ±0.05MPa.

[0018] Beneficial effects: Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects: 1. In the durable antibacterial nylon composite fiber of the present invention, the silver ion content of the inorganic antibacterial agent silver zeolite is appropriate and distributed in a specific gradient, ensuring the long-term stable release of silver ions and providing lasting antibacterial performance. The antibacterial agent is evenly and discretely distributed in the fiber, regularly arranged in three-dimensional space, with high consistency in different positions, which can effectively inhibit the growth of bacteria and is widely used in the fields of antibacterial textiles. At the same time, the antibacterial agent distribution state of the fiber is stable, and its radial distribution density function and length distribution characteristics ensure the uniformity and stability of the antibacterial effect in each part, thereby enhancing the antibacterial durability.

[0019] 2. The molecular weight and molecular chain structure characteristics of the nylon matrix material in the present invention lay a good foundation for the strength and toughness of the fiber. The average fiber length and reasonable length distribution make its processing performance stable and the cross-sectional shape regular, with high roundness, small fluctuation of the center of the circle, uniform density distribution, small deviation of the approximately circular cross-section, and uniform stress distribution when subjected to force, which significantly improves the mechanical properties of the fiber and its products, such as tensile strength and wear resistance. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The present invention will be further described below in conjunction with the embodiments.

[0022] Processing technology of durable antibacterial nylon composite fiber: Mixing step (S100): Equipment preparation: Use a specially designed high-speed mixer with a mixing barrel volume of 50-200L. The barrel wall is made of stainless steel 304 and the inner wall is equipped with a unique spoiler structure, which consists of spiral protrusions and grooves. The protrusion height is between 2-5mm, the groove depth is 1-3mm, the protrusion and groove widths are both 2-5mm, and the pitch is 10-20mm. This design helps to enhance the mixing effect of the materials during the mixing process.

[0023] Material weighing and addition: accurately weigh antimicrobial agents, dispersants, coupling agents and other additives to ensure that the weighing error is controlled within ±0.1%, and then add these materials into the mixing barrel. The mixing barrel is equipped with a temperature sensor with an accuracy of ±0.5℃. The temperature in the barrel is maintained at 40-60℃ through an external heating jacket. This temperature range helps to improve the fluidity and mixing performance of the material, while avoiding deterioration or chemical reactions of certain ingredients due to excessive temperature. Mixing operation: Start the mixer and mix at a high speed of 1000-2000 rpm for 10-20 minutes. The mixing paddle adopts a double-layer three-blade design. The paddle inclination angle is 30-60°, and a gap of 5-10mm is maintained between the paddle and the inner wall of the mixing barrel. During the mixing process, the materials are fully mixed under the action of the high-speed rotating paddles. At the same time, the turbulent structure further causes the materials to form a complex flow path in the barrel, thereby achieving uniform mixing and finally obtaining a uniform mixed powder.

[0024] Blending extrusion step (S200): Extruder equipment parameters: A twin-screw extruder is used for blending and extrusion operations. The screw diameter of the twin-screw extruder is 30-60mm, the screw aspect ratio is 30-40:1, the screw is made of high-strength alloy steel, the hardness reaches HRC50-60, the surface is nitrided, the depth of the nitriding layer is 0.1-0.3mm, and the surface roughness is controlled between 0.05-0.1μm. These parameters ensure that the screw has good wear resistance, corrosion resistance and shear mixing ability during the extrusion process, and can effectively mix and extrude various materials evenly.

[0025] Screw operation and temperature control: The screws rotate in the same direction, and the speed can be precisely controlled within the range of 100-300 rpm, with a control accuracy of ±1 rpm. The screw is divided into a feeding section, a compression section, a melting section and a metering section, and the length ratio of each section is 1:2:3:2. In the feeding section, the pitch is 30-40mm, the screw groove depth is 5-10mm, and the temperature is controlled at 200-220℃. A vacuum feeding system is used, and the feeding accuracy reaches ±0.5%. The vacuum feeding system can effectively prevent air from mixing into the material, ensuring the stability of the extrusion process and product quality. In the compression section, the pitch gradually decreases to 20-30mm, the screw groove depth is correspondingly reduced to 3-6mm, and the temperature rises to 230-250℃. The compression ratio is 2-3. During this process, the material is subjected to gradually increasing pressure and shear force to achieve further mixing and compaction. In the melting section, the temperature is further increased to 240-260°C. The temperature and pressure changes of the material are monitored in real time by installing a temperature sensor with an accuracy of ±0.5°C inside the screw and a pressure sensor with a monitoring range of 0-100MPa and an accuracy of ±0.1MPa to ensure that the material is completely melted and in a stable extrusion state. In the metering section, the pitch and screw groove depth remain stable, which are 20-30mm and 3-6mm respectively, and the temperature is 250-270°C. The material extrusion amount is accurately controlled by precisely adjusting the screw speed and back pressure, and the extrusion amount control accuracy is ±1%.

[0026] Co-blending extrusion process: the mixed powder obtained in step S100 and the nylon matrix material are added to the twin-screw extruder through their respective feeding ports. Under the rotation of the screw, the material is transported forward along the screw, and experiences different temperature, pressure and shear conditions in each section. In the feeding section, the material is preliminarily mixed and preheated; in the compression section, the material is compacted and further mixed; in the melting section, the material is completely melted and reaches a uniform state; in the metering section, the precisely controlled extrusion amount ensures the stable output of the melt. Finally, under the shearing, mixing and conveying action of the screw, the mixed powder and the nylon matrix material are co-blended and extruded to form a uniform melt.

[0027] Spinning step (S300): Spinning manifold and melt delivery: melt spinning method is adopted, and the melt temperature is stabilized at 240-270℃ by using a spinning manifold with an electric heating power of 10-30kW and a temperature control accuracy of ±1℃. The melt obtained in step S200 is delivered to the spinning assembly at a stable flow rate through a metering pump with a flow accuracy of ±0.5% and a displacement of 0.1-10ml / r. Accurate temperature control and stable melt delivery are key factors to ensure the smooth spinning process and stable fiber quality. Filter device: The filter device in the spinning assembly is composed of multiple layers of stainless steel 316L filter screens. The mesh sizes are 200, 400 and 600 from the feed end to the discharge end. The thickness of each layer of filter screen is 0.1-0.3mm, and the distance between adjacent filter screens is 2-5mm. This multi-layer filter screen structure can effectively filter impurities in the melt. The filtration efficiency of impurities in the melt is greater than 99%, ensuring that the fiber quality and spinning continuity will not be affected by impurities blocking the spinneret during the spinning process. Distribution plate and melt flow: The melt passes through a distribution plate with a thickness of 5-10mm. The distribution plate surface is provided with guide grooves. The depth of the guide grooves increases linearly from 0.5-1mm at the feed end to 1-2mm at the discharge end, and the width increases from 2-3mm at the feed end to 3-5mm at the discharge end. The total number of guide grooves is 10-30 and they are evenly distributed. The spacing between adjacent guide grooves is 5-10mm. The melt flows at a speed of 0.1-0.5m / s in the guide grooves. The design of the guide grooves enables the melt to be more evenly distributed before entering the spinneret, further improving the quality uniformity of the fiber.

[0028] Spinneret and spinning: The melt is finally spun through a spinneret with a thickness of 3-6mm. The diameter of the spinneret holes is between 10-50μm, the number of spinnerets is 100-1000 and they are arranged in a circle, the center distance between adjacent spinnerets is 0.5-2mm, the inner wall of the spinneret holes is electrochemically polished, and the surface roughness is less than 0.2μm. At a spinning speed of 1000-3000 m / min, the melt is extruded from the spinneret holes to form fibers. High-quality spinnerets and appropriate spinning speeds ensure the uniformity of fiber diameter and surface smoothness.

[0029] Post-processing step (S400): Cooling (S410): The spun fibers are cooled by cooling air provided by an air treatment system. The air treatment system includes an air filter with a filtration accuracy of 0.1-0.5μm, a heater with a heating power of 5-15kW and a temperature adjustment accuracy of ±0.5℃, a humidifier that can control the air humidity at 40-60%, and a fan with an air volume of 1000-5000m³ / h and a wind speed that can be adjusted within the range of 0.5-1.5m / s and an adjustment accuracy of ±0.05m / s. After strict treatment, the cooling air can cool and shape the fibers in a stable environment to avoid uneven fiber structure and performance due to fluctuations in cooling conditions.

[0030] Oiling (S420): The cooled fiber is oiled on an oil roller oiling device, the diameter of the oil roller is 100-300mm, the length is 200-500mm, the surface rubber hardness is Shore A60-80, the rotation speed is 50-100 rpm, the oiling agent is a mixed oil agent with a mass ratio of 3:1:1 of silicone oil, antistatic agent and bioactive additive, and the oiling rate is 0.5-1.5%. The oiling agent is formed into an oil mist with a particle size of 1-5μm by an ultrasonic atomization device and evenly adhered to the fiber surface. The oiling treatment can not only improve the feel of the fiber, but also improve the antistatic performance and spinnability of the fiber. At the same time, the bioactive additive may give the fiber some special functions.

[0031] Stretching (S430): The oiled fiber is stretched between multiple sets of stretching rollers. The diameter of the stretching rollers is 50-100mm, the surface is chrome-plated, the roughness is 0.05-0.1μm, the spacing between each set of stretching rollers is 100-300mm, the stretching multiple is 3-5 times, and the stretching temperature is 70-90℃. The stretching process is achieved by precisely controlling the roller speed (accuracy is ±0.5 rpm) and tension (accuracy is ±0.1N). The stretching operation helps to improve the orientation and strength of the fiber, so that the fiber obtains better physical properties.

[0032] Curling (S440): The stretched fiber is curled in a crimping machine. The diameter of the crimping wheel is 200-500mm. The surface has a special texture. The texture depth is 0.1-0.3mm, the texture spacing is 1-3mm, the crimping temperature is 80-100℃, and the curling degree is 10-20 / 25mm. The crimping process is achieved by precisely controlling the crimping wheel speed (accuracy is ±1 rpm) and pressure (accuracy is ±0.05MPa). The crimping process gives the fiber a certain degree of curl, increases the cohesion and fluffiness between the fibers, improves the feel and processability of the fiber, and finally obtains a durable antibacterial nylon composite fiber product.

[0033] Example of durable antibacterial nylon composite fiber: Embodiment 1: Ingredient preparation: Nylon matrix material: Polyamide 6 is selected as the nylon matrix material, with a number average molecular weight of 15,000, a weight average molecular weight of 30,000, an amide bond content of 95% in the molecular chain, a terminal carboxyl content of 0.3%, and an amino content of 0.15%, accounting for 80% of the total fiber weight.

[0034] Antibacterial agent: Inorganic antibacterial agent silver zeolite is used, with an average particle size of 1μm, a silver ion content of 3%, a cubic crystal structure, a lattice constant of 1.5nm, and a surface roughness of 0.2μm. The distribution of silver ions in zeolite crystals has a specific gradient, and the silver ion concentration gradually decreases from the crystal surface to the interior. It accounts for 10% of the total fiber weight.

[0035] Dispersant: Polyethylene glycol is used as a dispersant, with a molecular weight of 6000, a linear molecular chain, a degree of polymerization of 135, and hydroxyl end capping at both ends. Its mass ratio to the antibacterial agent is 1:3. It accounts for 3% of the total fiber weight.

[0036] Coupling agent: Titanate coupling agent is selected. The long-chain alkyl in the molecular structure is 12 carbon atoms and contains 3 active groups (carboxyl and phosphate). The molar ratio of coupling agent to antibacterial agent is 1:2. It accounts for 2% of the total weight of the fiber.

[0037] Other additives: including hindered phenolic antioxidants (content 2%) and calcium stearate (content 1%). The chemical structure of the antioxidant contains phenolic hydroxyl and tert-butyl substituents, and the particle size of calcium stearate is 3μm. It accounts for 3% of the total weight of the fiber.

[0038] Fiber characteristics analysis: Antimicrobial agent distribution status: In the three-dimensional space of the fiber, the antimicrobial agent exists in the nylon matrix material in the form of discrete particles. After establishing the polar coordinate system, the radial distribution density function of the antimicrobial agent particles is In the fiber length direction, there is an antibacterial agent particle every 15 μm on average, and the standard deviation of the distribution is 3 μm.

[0039] From a microscopic perspective, the thickness of the interface layer between the antimicrobial agent particles and the nylon matrix is ​​0.03μm, and the concentration gradient change rate of the coupling agent in the interface layer is 0.3mol / cm³・μm. High-resolution transmission electron microscopy observations show that there is no agglomeration between the antimicrobial agent particles and the matrix. Samples taken at different locations show a difference of less than 3%.

[0040] Cross-sectional shape: The overall cross-section is circular with a diameter of 30μm and a circularity of 0.95. The center position fluctuates within ±0.3μm in the axial direction of the fiber. From the center to the edge in the radial direction, the fiber density distribution is centrally symmetrical, and the density change rate is 3% / μm.

[0041] Surface structure: The thickness of the fiber surface covering layer is 0.3μm, and the proportion of the covering layer components changes gradiently in the depth direction. The lubricant component content in the outer layer is 70%, which gradually decreases toward the inner layer, and the antioxidant component content decreases from 80% to 30% from the inside to the outside.

[0042] The height difference of the surface covering layer is 30nm, the wavelength of the undulation is 100nm, and the repeating unit of the undulating structure pattern is a hexagon with a side length of 100nm. The diameter of the microscopic holes on the surface is 5nm and the density is 5×10 7 / cm², and the entropy value is 0.8 through gray-level co-occurrence matrix analysis.

[0043] Length and length distribution: The average fiber length is 60 mm, the length distribution conforms to the log-normal distribution, and the position parameter , scale parameter The measurement error of the laser particle size analyzer is within ±1.5mm. The measurement statistics of 1500 fiber samples show that the length distribution skewness is 0 and the kurtosis is 3.

[0044] Example 2: Preparation of ingredients: Nylon matrix material: polyamide 66, number average molecular weight is 20,000, weight average molecular weight is 40,000, amide bond content is 96%, carboxyl content is 0.4%, amino content is 0.2%, accounting for 75% of the total fiber weight.

[0045] Antimicrobial agent: silver zeolite, average particle size 1.5 μm, silver ion content 4%, lattice constant 1.8 nm, roughness 0.25 μm, accounting for 12% of the total fiber weight.

[0046] Dispersant: polyethylene glycol, molecular weight 7000, degree of polymerization 150, mass ratio with antibacterial agent 1:4, accounting for 3% of the total weight of the fiber.

[0047] Coupling agent: titanate coupling agent, alkyl chain length of 15 carbon atoms, 3 active groups, molar ratio with antibacterial agent 1:2.5, accounting for 2.5% of the total weight of the fiber.

[0048] Other additives: antioxidant content 2.5%, calcium stearate content 1.5%, antioxidant structure contains phenolic hydroxyl and tert-butyl, calcium stearate particle size 4μm, accounting for 4% of the total fiber weight.

[0049] Fiber characteristics analysis: Antimicrobial agent distribution status: Radial distribution density function of antimicrobial particles in polar coordinate system In the fiber length direction, there is an average of one antimicrobial agent particle every 18μm, with a standard deviation of 4μm. The thickness of the interface layer is 0.04μm, the gradient change rate of the coupling agent concentration is 0.4mol / cm³・μm, and the difference in sampling at different positions is less than 4%.

[0050] Cross-sectional shape: Circular cross section, diameter 35μm, circularity 0.96. Axial fluctuation of the center of the circle ±0.4μm, density change rate in the radial direction 4% / μm.

[0051] Surface structure: The thickness of the cover layer is 0.4 μm, the lubricant content of the outer layer is 75%, and the antioxidant content decreases from 80% to 25% from the inside to the outside. The height difference of the undulation is 40 nm, the wavelength is 150 nm, and the pattern repeating unit is a rectangle with a side length of 120 nm. The hole diameter is 8 nm and the density is 8×10 7 / cm², entropy value 0.9.

[0052] Length and length distribution: Average length 70mm, log-normal distribution , , measurement error ±1.8mm, skewness of 2000 fiber samples measured was 0.2, and kurtosis was 3.5.

[0053] Example 3: Ingredient preparation: Nylon matrix material: polyamide 6, number average molecular weight 18000, weight average molecular weight 35000, amide bond content 94%, carboxyl content 0.35%, amino content 0.18%, accounting for 85% of the total fiber weight.

[0054] Antimicrobial agent: silver zeolite, average particle size 1.2 μm, silver ion content 3.5%, lattice constant 1.6 nm, roughness 0.15 μm, accounting for 8% of the total fiber weight.

[0055] Dispersant: polyethylene glycol, molecular weight 5000, degree of polymerization 110, mass ratio with antibacterial agent 1:3.5, accounting for 2% of the total weight of the fiber.

[0056] Coupling agent: titanate coupling agent, alkyl chain length of 10 carbon atoms, 2 active groups, molar ratio with antibacterial agent 1:1.5, accounting for 1.5% of the total fiber weight.

[0057] Other additives: antioxidant content 1.5%, calcium stearate content 1%, antioxidant structure contains phenolic hydroxyl and tert-butyl, calcium stearate particle size 2μm, accounting for 2.5% of the total fiber weight.

[0058] Fiber characteristics analysis: Antimicrobial agent distribution status: Radial distribution density function In the fiber length direction, there is an average of one antimicrobial agent particle every 12μm, with a standard deviation of 2.5μm. The thickness of the interface layer is 0.02μm, the gradient change rate of the coupling agent concentration is 0.2mol / cm³・μm, and the difference in sampling at different positions is less than 2%.

[0059] Cross-sectional shape: Circular cross section, diameter 25μm, circularity 0.93. Axial fluctuation of the center of the circle ±0.2μm, density change rate in the radial direction 2% / μm.

[0060] Surface structure: The thickness of the cover layer is 0.2 μm, the lubricant content of the outer layer is 65%, and the antioxidant content decreases from 80% to 35% from the inside to the outside. The height difference of the undulation is 20 nm, the wavelength is 80 nm, and the pattern repeating unit is a hexagon with a side length of 80 nm. The hole diameter is 3 nm and the density is 3×10 7 / cm², entropy value 0.6.

[0061] Length and length distribution: Average length 45mm, log-normal distribution , , measurement error ±1.2mm, skewness of 1200 fiber samples measured -0.3, kurtosis 2.5.

[0062] The above embodiments are compared and analyzed, and the analysis results are as follows: Table 1: Comparison of antimicrobial distribution-related characteristics

[0063] Table 1: Radial distribution density function parameters of antibacterial agent in Example 2 and Relatively large, The distribution of the antimicrobial agent on the fiber cross section is relatively concentrated near the center and decays faster. In the fiber length direction, the antimicrobial agent particles of Example 2 have the largest spacing and the largest standard deviation, indicating that their distribution is relatively dispersed. The interface layer thickness and coupling agent concentration gradient change rate of Example 2 are the largest, which affects the combination of the antimicrobial agent and the matrix. Example 3 shows relatively low values ​​in some parameters, such as , and etc., the antimicrobial agent distribution and interface layer characteristics thereof are different from those of embodiments 1 and 2.

[0064] Table 2: Comparison of cross-sectional shape related properties

[0065] In Table 2: the cross-sectional circularity of Example 2 is the highest, closest to the ideal circle, the axial fluctuation range of the center of the circle is relatively large, and the density change rate in the radial direction is also the largest, indicating that its cross-sectional shape has good regularity but has certain characteristics in the axial and radial density uniformity; the circularity of Example 3 is relatively low, the axial fluctuation range of the center of the circle is the smallest, and the density change rate in the radial direction is the smallest, and its cross-sectional shape and density distribution are different from the other two examples; Example 1 is at an intermediate level in these characteristics and has good comprehensive performance.

[0066] Table 3: Comparison of surface structure related characteristics

[0067] In Table 3: Example 2 has the thickest surface covering layer, the highest outer layer lubricant content, larger undulation height difference and wavelength, relatively larger microscopic hole diameter and density, and the highest entropy value, indicating that its surface structure is relatively rougher and the hole characteristics are more obvious, which may affect the fiber's feel, adsorption and other properties; Example 3 has the smallest surface covering layer thickness, the lowest outer layer lubricant content, relatively small undulation and hole-related parameters, and a relatively smoother surface; Example 1 is between the two in these surface structure characteristics, and has moderate surface properties.

[0068] Table 4: Comparison of fiber length and length distribution related characteristics

[0069] In Table 4: The average fiber length of Example 2 is the longest, and the log-normal distribution position parameter and scale parameter The maximum value has the largest measurement error. The length distribution skewness is positive and the kurtosis is high, indicating that its length distribution is relatively more dispersed and skewed to the right, and the proportion of long fibers is relatively high. The average length of Example 3 is the shortest. and The smallest, the smallest measurement error, the negative skewness, the lowest kurtosis, its length distribution is relatively more concentrated and skewed to the left, and the proportion of short fibers is relatively high; Example 1 is between the two in terms of fiber length and length distribution characteristics, and has a more balanced length characteristic.

[0070] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A durable antibacterial nylon composite fiber, characterized in that: The composite fiber includes the following components: Nylon matrix material: accounting for 70-90% of the total weight of the fiber, the nylon matrix material is polyamide 6 or polyamide 66, with a number average molecular weight of 10,000-30,000, a weight average molecular weight of 20,000-50,000, an amide bond content of 90-98% in the molecular chain, and terminal groups including carboxyl and amino groups, with a carboxyl content of 0.1-0.5% and an amino content of 0.05-0.3%; Antimicrobial agent: accounting for 5-20% of the total weight of the fiber, it is an inorganic antimicrobial agent silver zeolite, with an average particle size of 0.5-2μm and a silver ion content of 2-5%. The crystal structure of silver zeolite is cubic, with a lattice constant of 1-2nm. Its surface has a specific microscopic morphology, with a roughness of 0.1-0.3μm, and the distribution of silver ions in the zeolite crystal has a specific gradient, with the concentration of silver ions gradually decreasing from the crystal surface to the interior; Dispersant: accounting for 2-5% of the total weight of the fiber, it is polyethylene glycol, with a molecular weight of 4000-8000, a linear molecular chain, a degree of polymerization of 90-180, and hydroxyl end-capping at both ends. Its dispersion mechanism in the fiber preparation process is based on steric hindrance effect and hydrogen bonding with other components. The mass ratio of dispersant to antibacterial agent is between 1:2-1:5; Coupling agent: accounting for 1-3% of the total weight of the fiber, it is a titanate coupling agent, its molecular structure contains a long-chain alkyl group, the length of the alkyl chain is 8-18 carbon atoms, and it also contains multiple active groups, including carboxyl and phosphate groups, the number of active groups is 2-4, and the molar ratio of the coupling agent to the antibacterial agent is 1:1-1:3; Other additives: accounting for 2-5% of the total weight of the fiber, including antioxidants and lubricants. The antioxidant is a hindered phenol antioxidant, and its chemical structure contains phenolic hydroxyl groups and specific substituents. The substituents include tert-butyl, and the content is 1-3%. The lubricant is calcium stearate, and its particle size is between 1-5μm, and the content is 1-2%.

2. The durable antibacterial nylon composite fiber according to claim 1, characterized in that: The distribution state of the antimicrobial agent is characterized by: In the three-dimensional space of the fiber, the antimicrobial agent exists in the nylon matrix material in the form of discrete particles. The particles are distributed on the cross section of the fiber. A polar coordinate system is established with the center of the circle as the origin. The radial distribution density function of the antimicrobial agent particles is: ,in , , is a constant, is the radius, the angular distribution is uniform, and in the fiber length direction, the distribution of antimicrobial particles conforms to the Poisson distribution, with an average of one particle every 10-20 μm, and a standard deviation of 2-5 μm; From a microscopic perspective, there is an interface layer with a thickness of 0.01-0.05μm between the antimicrobial agent particles and the nylon matrix. This interface layer is formed by the interaction between the coupling agent, the matrix and the antimicrobial agent. The concentration of the coupling agent in the interface layer changes gradually from the surface of the antimicrobial agent to the inside of the matrix, and the gradient change rate is 1-0.5mol / cm³・μm. High-resolution transmission electron microscopy observations showed that there was no agglomeration between the antimicrobial particles and the matrix, and sampling at different positions of the fiber showed that the distribution of the antimicrobial particles was highly consistent, with the difference between the sampling positions being less than 5%.

3. The durable antibacterial nylon composite fiber according to claim 1, characterized in that: The cross-sectional shape of the composite fiber has the following characteristics: The cross section is circular or approximately circular, the diameter of the circle is between 10-50 μm, the circularity is between 0.9-1.0, and the circularity calculation formula is: circularity = 4×Π(cross-sectional area) / (circumference²); For circular cross-sections, the fluctuation range of the center position in the axial direction of the fiber is within ±0.5μm, and in the cross-section, the fiber density distribution is centrally symmetrical in the radial direction from the center to the edge, and the density change rate is less than 5% / μm; For the approximately circular cross section, the deviation of its profile from the ideal circle is quantified by the Fourier descriptor. The sum of the absolute values ​​of the first five-order Fourier descriptors is less than 0.1, and the change of this deviation along the fiber length direction is continuous and slow, with a rate of change of less than 0.01 / μm. The boundary of the cross section has specific microscopic geometric characteristics, the average curvature of the boundary is between 0.1-1.0μm-1, and the curvature change at each point on the boundary is continuous, and there is no curvature mutation point.

4. The durable antibacterial nylon composite fiber according to claim 1, characterized in that: The surface structure of the composite fiber has the following characteristics: There is a covering layer with a thickness of 0.1-0.5μm on the fiber surface. This covering layer is composed of multiple components, including some additives that migrate from the inside of the fiber to the surface and substances formed by the interaction with the external environment during processing. The composition ratio of the covering layer changes gradually in the depth direction. The lubricant content in the outer layer close to the fiber surface is higher, accounting for 60-80%, and gradually decreases toward the inner layer, while the antioxidant content is the opposite, decreasing from 80% to 20% from the inside to the outside; The fiber surface covering layer has a nanoscale undulating structure, the height difference of the undulation is between 10-50nm, the wavelength of the undulation is between 50-200nm, and the undulating structure shows a regular pattern under atomic force microscopy. The repeating unit of the pattern is a hexagon or rectangle with a side length between 50-150nm. There are microscopic holes on the surface of the covering layer, the diameter of the holes is between 1-10nm, and the density of the holes is 10 6 -10 8 The holes are evenly distributed on the fiber surface, and the uniformity of the distribution is analyzed by gray-level co-occurrence matrix, with an entropy value between 0.5 and 1.

0.

5. The durable antibacterial nylon composite fiber according to claim 1, characterized in that: The length and length distribution of the composite fiber have the following characteristics: The average length of the fiber is between 30 and 100 mm, and its length distribution conforms to the log-normal distribution. The parameters of the log-normal distribution are: the position parameter μ is between 3 and 5, and the scale parameter σ is between 0.5 and 1.0; The fiber length was measured by a laser particle size analyzer with a measurement error within ±2 mm. The fiber sample quantity was greater than 1000 and the skewness of the length distribution was between -0.5 and 0.5, and the kurtosis was between 2 and 4, which ensured the normality of the fiber length distribution. During the fiber production process, the fiber length is controlled by the cutting process. The tool movement accuracy of the cutting equipment is within ±0.1mm, and the tensile or compressive deformation of the fiber during the cutting process is less than 5%.

6. A process for processing a durable antibacterial nylon composite fiber according to any one of claims 1 to 5, characterized in that: The specific steps of this processing technology are: S100: a mixing step, in which the antimicrobial agent, dispersant, coupling agent and other additives are mixed in a specific proportion to form a uniform mixed powder; S200: a blending and extruding step, blending and extruding the mixed powder and the nylon matrix material to obtain a melt; S300: Spinning step, allowing the melt to pass through a spinning assembly to form fibers; S400: post-processing step, cooling, oiling, stretching and curling the fiber in sequence, and finally obtaining a durable antibacterial nylon composite fiber.

7. The processing technology of the durable antibacterial nylon composite fiber according to claim 6, characterized in that: The S100 steps are as follows: S110: Use a specially designed high-speed mixer with a mixing barrel volume of 50-200L. The barrel wall material is stainless steel 304. The inner wall is equipped with a spoiler structure, which consists of a spiral protrusion height of 2-5mm and a groove depth of 1-3mm. The width of the protrusion and groove are both 2-5mm, and the pitch is 10-20mm. S120: Precisely weigh antimicrobial agents, dispersants, coupling agents and other additives within a weighing error of ±0.1%, and then add them to a mixing barrel. The mixing barrel is equipped with a temperature sensor with an accuracy of ±0.5°C, and the temperature in the barrel is maintained at 40-60°C through an external heating jacket; S130: Start the mixer and stir at a speed of 1000-2000 rpm for 10-20 minutes. The stirring paddle is a double-layer three-blade type with a blade inclination angle of 30-60° and a gap of 5-10mm between the blade and the inner wall of the mixing barrel, so that the materials are fully mixed to form a uniform mixed powder.

8. The processing technology of the durable antibacterial nylon composite fiber according to claim 6, characterized in that: The S200 steps are as follows: S210: Blending and extrusion are carried out in a twin-screw extruder, the screw diameter of the twin-screw extruder is 30-60mm, the screw aspect ratio is 30-40:1, the screw material is high-strength alloy steel, the hardness is HRC50-60, the surface is nitrided, the nitrided layer depth is 0.1-0.3mm, and the surface roughness is 0.05-0.1μm; S220: The screws rotate in the same direction, and the speed can be adjusted within the range of 100-300 rpm, with an adjustment accuracy of ±1 rpm. The screw is divided into a feeding section, a compression section, a melting section and a metering section, and the length ratio of each section is 1:2:3:

2. In the feeding section, the pitch is 30-40mm, the screw groove depth is 5-10mm, the temperature is controlled at 200-220℃, and a vacuum feeding system is used. The feeding accuracy is ±0.5%. In the compression section, the pitch is gradually reduced to 20-30mm, and the screw groove depth is correspondingly reduced to 3-6mm. The temperature Increase to 230-250℃, compression ratio is 2-3, in the melting section, the temperature is further increased to 240-260℃, and real-time monitoring is carried out by a temperature sensor with an accuracy of ±0.5℃ and a pressure sensor with a monitoring range of 0-100MPa and an accuracy of ±0.1MPa installed inside the screw. In the metering section, the pitch and screw groove depth remain stable, 20-30mm and 3-6mm respectively, the temperature is 250-270℃, and the material extrusion amount is accurately controlled by adjusting the screw speed and back pressure, and the extrusion amount control accuracy is ±1%; S230: adding the mixed powder obtained in step S100 and the nylon matrix material into the twin-screw extruder through respective feeding ports, and achieving co-extrusion under the shearing, mixing and conveying action of the screw to form a uniform melt.

9. The processing technology of the durable antibacterial nylon composite fiber according to claim 6, characterized in that: The S300 steps are as follows: S310: melt spinning method is adopted, the temperature of the spinning box is stabilized at 240-270°C by using an electric heating power of 10-30kW and a temperature control accuracy of ±1°C, and the melt obtained in step S200 is delivered to the spinning assembly at a stable flow rate by a metering pump with a flow accuracy of ±0.5% and a displacement of 0.1-10ml / r; S320: The filtering device in the spinning assembly is composed of multiple layers of stainless steel 316L filter screens, with mesh sizes of 200, 400 and 600 from the feed end to the discharge end. The thickness of each layer of filter screen is 0.1-0.3mm, and the spacing between adjacent filter screens is 2-5mm. The filtering efficiency of impurities in the melt is greater than 99%; S330: The melt passes through a distribution plate with a thickness of 5-10 mm. A guide groove is provided on the surface of the distribution plate. The depth of the guide groove increases linearly from 0.5-1 mm at the feed end to 1-2 mm at the discharge end, and the width increases from 2-3 mm at the feed end to 3-5 mm at the discharge end. The total number of guide grooves is 10-30 and is evenly distributed. The spacing between adjacent guide grooves is 5-10 mm. The flow rate of the melt in the guide groove is 0.1-0.5 m / s. S340: The melt finally passes through a spinneret, which has a thickness of 3-6 mm, a spinneret hole diameter of 10-50 μm, 100-1000 spinnerets arranged in a circle, and a center distance of adjacent spinnerets of 0.5-2 mm. The inner wall of the spinneret hole is electrochemically polished, and the surface roughness is less than 0.2 μm. Fibers are formed at a spinning speed of 1000-3000 m / min.

10. The processing technology of the durable antibacterial nylon composite fiber according to claim 6, characterized in that: The S400 steps are as follows: S410: Cooling. The spun fibers are cooled by cooling air provided by the air treatment system. The air treatment system includes an air filter with a filtration accuracy of 0.1-0.5μm, a heating power of 5-15kW, a temperature adjustment accuracy of ±0.5℃, a heater that can control the temperature at 15-25℃, a humidifier that can control the air humidity at 40-60%, and an air volume of 1000-5000m³ / h. The wind speed can be adjusted within the range of 0.5-1.5m / s, and the adjustment accuracy is ±0.05m / s. The fan allows the fibers to be cooled and shaped in a stable environment; S420: Oiling: the cooled fiber is oiled on an oil roller oiling device with an oil roller diameter of 100-300 mm, a length of 200-500 mm, a surface rubber hardness of Shore A60-80, and a rotation speed of 50-100 rpm. The oiling agent is a mixed oil agent with a mass ratio of 3:1:1 of silicone oil, antistatic agent and bioactive additive, and the oiling rate is 0.5-1.5%. The oiling agent is formed into an oil mist with a particle size of 1-5 μm by an ultrasonic atomization device and uniformly adhered to the fiber surface; S430: Stretching: the oiled fiber is stretched between multiple sets of stretching rollers with a diameter of 50-100 mm, chrome-plated surface, roughness of 0.05-0.1 μm, and a spacing of 100-300 mm between each set of stretching rollers. The stretching multiple is 3-5 times, and the stretching temperature is 70-90°C. The stretching is achieved by precisely controlling the roller speed and tension, where the speed accuracy is ±0.5 rpm and the tension accuracy is ±0.1N. S440: Curling: The stretched fiber is curled in a crimping machine with a crimping wheel diameter of 200-500mm, a special texture on the surface, a texture depth of 0.1-0.3mm, and a texture spacing of 1-3mm. The crimping temperature is 80-100℃, and the crimping degree is 10-20 / 25mm. The crimping is achieved by precisely controlling the crimping wheel speed and pressure, with a speed accuracy of ±1 rpm and a pressure accuracy of ±0.05MPa.

Citation Information

Cited By

  • An antibacterial regenerated polyamide 6, its preparation method and application

    CN120665279B